Experimental investigation on HSFP using MWCNT based nanofluids for high power light emitting diodes - B., Sangmesh; K., Gopalakrishna; S. H., Manjunath; N., Kathyayini; K., Kadirgama; Mahendran, Samykano; Vijayakumar, G. C. (Faculty Mechanical Engineering, UMP, 2018)
LEDs, of late, have received attention as the next generation lighting system for enhanced luminous efficiency and higher lifespan. However, the thermal management of the LEDs is the crucial parameter to be countered for global acceptance as a revolutionary illumination source. This paper reports the experimental investigation of natural convective heat transfer of high power LED COBs using MWCNT and MWCNT-CuO nanofluids mixed with de-ionized water. The study uses MWCNT based nanofluids as a route to enhance the heat transfer of high power LEDs by the passive cooling technique. This study presents an innovative cooling device integrated with numerous fluid pockets, called the HSFP, to achieve the enhanced thermal performance of heat sinks for applications in high intensity LED lights. Nanofluids of various concentrations were formulated and their heat transfer performance evaluated using a series of experiments and compared with liquid cooling and a conventional heat sink. The experimental finding reveals 20– 30% lowered thermal resistance using the new HSFP (nanofluids). Thus, the HSFP found to effectively dissipates the heat in high-power LED COBs using nanofluids as the cooling medium compared to the conventional heat sink.